Biochemical Testing Clinical Correlation and Diagnosis - Bobbarala, Varaprasad; Sarwar Zaman, Gaffar; Nasir Mohd Desa, Mohd; Md Akim, Abdah (Biochemistry, 2020)
Clinical Correlation and Diagnosis highlights the improvements in methodological approaches for the purposes of disease diagnosis and health research. Chapters cover such topics as serum protein electrophoresis, urinary iodine measurement, blood collection tubes, semi-solid phase assay and advancement in analytical and bioanalytical techniques, and serological diagnostic tools for Zika virus, among other subjects. All these will not be possible without a proper laboratory management where this book also includes the Tissue Bank ATMP Production as a model. The chapters are expected to provide a new perspective in health science which may trigger a further exploration into the diagnostic and research field.